Blockchain Depository Technology in Litigation Activities: – Introduction with the Way of Defending the Right in the Case of Network Infringement - Feng, Yueyao (Transactions on Social Science, Education and Humanities Research, 2023)
The development of the Internet has made the dissemination of information on the Internet much faster than before, and consequently caused the occurrence of cyber violence. In this series of events, the difficulty of the parties to defend their rights is regarded as a very prominent problem. A large part of the difficulty in defending the rights of the parties concerned is due to the difficulty in collecting evidence. According to the principle of "whoever claims, whoever produces evidence", the infringer needs to bear the unfavorable consequences of proof, thus making it difficult for infringers to defend their legitimate rights and interests in cyber violence infringement cases. With the development of blockchain technology, the problem of traditional electronic data forensics will be solved by blockchain technology. This paper will take the main logic of how blockchain evidence solves the dilemma of applying traditional electronic data in litigation activities, and take the way of defending rights in network infringement cases as the entry point to elaborate the application of blockchain deposit technology in litigation activities.